2015
DOI: 10.1007/s00431-015-2645-y
|View full text |Cite
|
Sign up to set email alerts
|

Problematic cell phone use for text messaging and substance abuse in early adolescence (11- to 13-year-olds)

Abstract: our findings confirm a widespread PCPU for text messaging among early adolescents. The odds of PCPU is greater in young people at risk of other substance abuse behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 33 publications
1
29
0
5
Order By: Relevance
“…Although a great deal of research has examined how text messaging may be harmful (Gallimberti et al, ; Nesi et al, ; Wolfe, Marcum, Higgins, & Ricketts, ), this platform may provide a technological means for navigating many of the traditional challenges of adolescence. These communication technologies are now firmly entrenched in modern society and are unlikely to go away, so understanding how youth can use them to navigate the developmental challenges of adolescence may be a critical step in promoting the healthy development of future generations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a great deal of research has examined how text messaging may be harmful (Gallimberti et al, ; Nesi et al, ; Wolfe, Marcum, Higgins, & Ricketts, ), this platform may provide a technological means for navigating many of the traditional challenges of adolescence. These communication technologies are now firmly entrenched in modern society and are unlikely to go away, so understanding how youth can use them to navigate the developmental challenges of adolescence may be a critical step in promoting the healthy development of future generations.…”
Section: Discussionmentioning
confidence: 99%
“…Most recent research on text messaging involves college or young adult samples (e.g., Holtzman et al, ; Hsieh & Tseng, ; Ishii, Rife, & Kagawa, ; McEwan & Horn, ; Ouelette & Michaud, ). Almost all studies rely on survey data (e.g., Abeele et al, ; Gallimberti et al, ; Grover et al, ; Ishii et al, ; Lenhart, ; Ling, ; McEwan & Horn, ; Nesi, Widman, Choukas‐Bradley, & Prinstein, ). However, important exceptions examine small samples of text messages of college students (Eshghinejad & Moini, ; Ouelette & Michaud, ) and young adults (Aledavood et al, ), as well as one laboratory study with college students (Holtzman et al, ).…”
Section: Empirical Investigations Of Adolescents’ Text Messagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile phone and Internet overuse may be harmful to the young person's health, causing stress, depression, social anxiety, insomnia or hyperactivity [7][8][9]. Moreover, studies show that emotional and behavioral problems are more frequent among adolescents who use the Internet or a mobile phone problematically [9][10][11][12], with some of the most popular forms of mobile phone use being surfing the Internet, playing games online or sending text messages [13]. The problematic use of mobile phones is associated with young age, extraversion, low level of conciliating attitudes, high level of depression and low self-evaluation [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Livingstone and Smith reviewed the potential risks of cyber‐aggression, cyber‐bullying and sexual misconduct through exchanges of abusive or sexually explicit text messages. Other studies have reported the risk of mental and physical problems being associated with the use of electronic devices such as television (TV) and video games, including internalising behaviours such as depression and externalising behaviours such as substance abuse, poor academic performance and obesity .…”
Section: Introductionmentioning
confidence: 99%